Pengaruh Beban Kerja dan Dukungan Sosial Terhadap Kinerja Karyawan dengan Burnout Sebagai Variabel Mediasi - Putri Sukowati; Padmantyo, Sri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to examine the influence of workload and social support on employee performance with burnout as a mediating variable. The study adopts a quantitative approach within a positivistic paradigm. Primary data were collected from 200 respondents using simple random sampling. Data analysis employed Partial Least Square (PLS) with tests for validity, reliability, multicollinearity, and structural model evaluation. The results indicate that workload does not significantly impact employee performance directly but contributes significantly to burnout. Burnout negatively affects employee performance and acts as a significant mediator between workload and performance. Conversely, social support positively influences performance and reduces the risk of burnout. Therefore, organizations need to manage workloads and provide adequate social support to create a healthier work environment and sustainably enhance employee performance.